Comparison of CT and fluoroscopic guidance for lumbar puncture in an obese population with prior failed unguided attempt. (1st June 2013) - Brook, Andrew D; Burns, Judah; Dauer, Edward; Schoendfeld, Alan H; Miller, Todd S
Abstract : Background and purpose: In the past 50 years, fluoroscopic guidance has been used to improve upon lumbar puncture (LP) technique that was unchanged for over a century. Recently, CT has seen increasing use as a guidance modality due to its ability to demonstrate soft tissue contrast and provide millimeter accuracy with needle targeting. This study compared procedure time and radiation dosages for fluoroscopic and CT guided LP. Materials and methods: This institutional review board and Health Insurance Portability and Accountability Act (HIPAA) compliant study was a retrospective review of a consecutive cohort referred for image guided LP. For CT, 45 patients aged 49 years (range 20–78, SD 14) with body mass index (BMI) values of 33 kg/m 2 (range 20–50, SD 12) were included. For fluoroscopy, 100 patients aged 47 years (range 18–88, SD 17) with BMI values of 29 kg/m 2 (range 15–56, SD 9) were included. CT procedure time was determined using picture archiving and communication system (PACS) image time stamps. Radiation dose was determined using the CT dose report and effective dose conversion factors. Fluoroscopic procedure time was determined from nursing. Fluoroscopic radiation dose was calculated from dose–area product (DAP) and fluoroscopy times, with effective dosage calculated using simulation software. Results: For CT, procedure time average was 14 min (range 5–42, SD 8.5). Average dose–length product was 120 mGy×cm (range 39–211, SD 43) and average effective dose was 1.98 mSv (range 0.2–8.18, SD 4.4). For fluoroscopy, procedure time averaged 12 min (range 12–30, SD 6). Average DAP was 10 Gy×cm 2 (range 0.1–70, SD 11) and effective dose estimate averaged 2.9 mSv (range 0.9–9.4, SD 1.9). There were no unsuccessful taps or complications. Conclusions: Both fluoroscopic and CT guidance may be used to perform an LP in an obese population with a short procedure time and low radiation dose.